SELF-ORIENTALISM REPACKAGED: WONG WING FRIED RICE: Received: 24th January 2023, Revised: 12th April 2023, 14th April 2023, Accepted: 21st April 2023 - Imani, Neela (PEOPLE: International Journal of Social Sciences, 2023)
Globalization has prompted a multicultural retheorization of both consumer and market (Fu et al., 2014; Riefler et al., 2012; Kipnis et al., 2019). In short, the Canadian multicultural market consists of international goods which are authentic, domestic goods purporting authenticity (e.g., orientalizing), and multinational, fusion innovations that are authentic-ish (e.g., self-orientalizing; Hui, 2019; Li, 2020; Stephens, 2021). What results is a fetishistic commercialization of multiculturalism, where brands are packaging ethnicity and race to vie for consumer attention. This paper addresses the latter variety — self-orientalist packaging designed for products born out of (formerly) Chinese Canadian enterprises, namely Wong Wing Fried Rice. Developing an analytical and theoretical approach that can support the identification of racialization, racist typologies are situated in graphic design. Themes derived from the analysis include racism, orientalism, self-orientalism, exoticism, cultural appropriation, among others. Findings reveal how self-orientalist packaging and label design is discursively negotiated as both internalized racism and anti-racist resistance, necessitating a more nuanced approach that reflects the sociopolitical context in which products are branded. The adoption of transversalist tenets, an anti-racist modality outlined by the methodological component of this study, presents one possibility.